Accessibility as a Conversation - Romero Fresco, Pablo; Dangerfield, Kate (Journal of Audiovisual Translation, 2022)
Film has a long-standing relationship with the notion of universality, which has often been used by Hollywood to perpetuate a dominant and unified worldview and to disseminate certain (Western) values that contribute to establishing what should and should not be considered normal, including the idea of the normative individual. Audiovisual translation and media accessibility could undermine the notion of universality in film; however, media accessibility has somehow reinstated this idea through reference to universal design and the use of the phrase “for all”. This can mask the exclusion of certain users who are not catered for by most mainstream accessibility guidelines. The first aim of this article is to explore how the notion of universality has been used in media accessibility and how it is reflected in official guidelines and in current practice. The second aim is to introduce the work of an emerging wave of (mostly disabled) artists who are proposing an alternative approach to media accessibility, one that is openly subjective, increasingly creative and that often works as a political tool in a wider fight against discrimination and for real inclusion. These artists consider access as a conversation involving meaningful contributions by disabled and non-disabled people. Lay summary The first aim of our article is to explore how the notion of universality has been used in film and especially in media accessibility. We also look at how this idea is reflected in official guidelines and in current practice. We focus on the examples of universal design and the phrase "for all", which are prevalent in the field of media accessibility. This way of thinking typically masks the exclusion of certain users who are not catered for by most mainstream accessibility guidelines. Media accessibility has the potential to challenge what is considered as "normal" and the second aim of our article is to introduce the work of an emerging wave of (mostly disabled) artists who are proposing an alternative approach to media accessibility. This approach is subjective, creative and often works as a political tool in a wider fight against discrimination and for real inclusion. These artists consider access as a conversation involving meaningful contributions by disabled and non-disabled people.